PROSEDUR PENYELESAIAN PERKARA HAK ASUH ANAK DALAM KASUS PERCERAIAN YANG MENGGUNAKAN KETENTUAN HUKUM ADAT BALI: Resolution Procedure for Child Custody Cases in Divorce Involving Balinese Customary Law Provisions - Batari Abdi Putri; Ning Adiasih (Faculty of Law, Universitas Trisakti, 2025)
In today's context, the issue of custody rights over children has become a significant concern in divorce proceedings. When deciding divorce cases, the panel of judges relies on the examination of the case itself, leading to varying judgments. As seen in Case Number: 152/Pdt/2019/PT DPS, there is a discrepancy between the results of mediation and the court's decision regarding custody rights. Through legal writing using the juridical-normative method, the identification of problems addressed in this writing are: 1) How do judges legally consider awarding custody rights in divorce cases? 2) What is the procedure for divorce lawsuits followed by claims for custody rights?. Based on the gathered data, the research findings iand conclusion ndicate that in deciding child custody cases, many factors are not taken into consideration by the panel of judges. One of these factors is the outcome of mediation efforts that adhere to customary law agreements. This does not reflect the principle of legal certainty in court decisions, as stipulated in Article 30 of PERMA No. 1 of 2016 regarding Mediation. Additionally, during the examination of witnesses in this case, it was found that the witnesses presented by the defendant did not meet the material qualifications as witnesses in civil procedural law, as regulated in Article 171 of the HIR.